The Role of Trust to Leading and Psychological Empowerment on Innovative Work Behavior in Knowledge Sharing Mediation for Batik Tulis MSME Workers - Elfia Nora; Sopiah Sopiah; Imam Bukhori (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Trust to leading, psychological empowerment, and knowledge sharing can give rise to innovative work behavior of workers, especially workers in Batik Tulis MSMEs. Research Objectives: Trust to leading (1) To test the influence of Trust to leading on knowledge sharing in Batik Tulis MSME workers, (2) to test the influence of Psychological empowerment on knowledge sharing in Batik Tulis MSME workers, (3) the influence of Trust to leading on innovative work behavior in Batik Tulis MSME workers, (4) to test the influence of Psychological empowerment on innovative work behavior in Batik Tulis MSME workers, (5) to examine the influence of knowledge sharing on innovative work behavior in Batik Tulis MSME Workers, (6) to examine the influence of Trust to leading on innovative work behavior through knowledge sharing in Batik Tulis MSME workers, (7) to examine the influence of Psychological empowerment on innovative work behavior through knowledge sharing in Batik Tulis MSME workers. The research is quantitative research with a sample of 75 workers in Batik Tulis MSMEs. The results showed that (1) there is a direct and significant influence of Trust to leading on knowledge sharing in Batik Tulis MSME workers, (2) there is a direct and significant influence of Psychological empowerment on knowledge sharing in Batik Tulis MSME workers, (3) there is a direct and significant influence of Trust to leading on innovative work behavior in Batik Tulis MSME workers, (4) there is a direct and significant influence of Psychological empowerment on innovative work behavior in Batik Tulis MSME workers, (5) there is a direct and significant influence of knowledge sharing on innovative work behavior in Batik Tulis MSME Workers, (6) there is an indirect influence of Trust to leading on innovative work behavior through knowledge sharing in Batik Tulis MSME workers, (7) there is an indirect influence of psychological empowerment on innovative work behavior through knowledge sharing in Batik Tulis MSME workers.